Alan L. Berger and David Patterson, with David P. Gushee, John T. Pawlikowski, and John K. Roth. Jewish-Christian Dialogue: Drawing Honey from the Rock - Boys, Mary C. (Studies in Christian-Jewish Relations, 2011)
No abstract is available.